2013
DOI: 10.1111/efp.12073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Ralstonia solanacearum infecting Eucalyptus spp. in Brazil

Abstract: Among the bacterial pathogens of Eucalyptus in Brazil, Ralstonia solanacearum is considered one of the most important because of the characteristics of the pathogen, like the high diversity among the strains related to host range, high virulence, broad geographical distribution and its damage to the crop in recent years. Given its importance and the lack of research on this pathosystem, the present study aimed to perform a molecular characterization of different strains of infected Eucalyptus plants in Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 27 publications
1
34
5
Order By: Relevance
“…Differences were seen for each gene region when those sequences from Colombia were compared to the sequences from those isolates used by Fonseca et al . () but the differences were less than 5%.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Differences were seen for each gene region when those sequences from Colombia were compared to the sequences from those isolates used by Fonseca et al . () but the differences were less than 5%.…”
Section: Resultsmentioning
confidence: 78%
“…Fonseca et al . () used phylotyping to classify R. solanacearum isolates that are associated with bacterial wilt of Eucalyptus in Brazil. Their results showed that the Brazilian isolates grouped into phylotype II.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to highlight that, in this review, some studies about the genetic variability of this bacterial population in Brazil report that the existence of diversity among strains oftentimes is correlated with its geographical origin (SILVEIRA et al, 2005;FONSECA et al, 2014), similarly to what was established for the classification into phylotypes. Therefore, the lower local bacterial variability allows disease control through the use of resistant cultivars recommended for each region of the country, although care should be taken against the dissemination of strains via propagation material.…”
Section: Genetic Diversity Of Ralstonia Solanacearum In Brazilmentioning
confidence: 53%
“…Classification into phylotypes is done by PCR Multiplex with the Nmult series primers (based on ITS region) and the classification into sequevar by partially sequencing gene egl (encoding the enzyme endoglucanase). Presently, four phylotypes and 51 sequevares of R. solanacearum are described (XU et al, 2009;FONSECA et al, 2014). Analysis of genetic diversity can be conducted based on repetitive sequences (rep-PCR), comprised by the elements BOX, ERIC, and REP, by randomly amplified DNA (RAPD), by amplification of restriction fragments (AFLP), repeated simple sequences (SSR) and by polymorphisms based on restriction fragment size (RFLP) (JAUNET;WANG, 1999;VANDEWALLE;LUISETTI, 1999;COENYE;VANDAMME, 2003;YU et al, 2003;KUMAR;SARMA;ANANDARAJ, 2004;SILVEIRA et al, 2005;LOPES, 2007;IVEY et al, 2007).…”
Section: Genetic Diversity Of Ralstonia Solanacearum In Brazilmentioning
confidence: 99%
See 1 more Smart Citation